Metagenome next-generation sequencing plays a key role in the diagnosis and selection of effective antibiotics on the treatment of Nocardia pneumonia: a case report - Fan, Na; Fang, Huang; Huang, Fang; Zhou, Jie; Liu, Peng; Li, Meng-Jie; Ding, Ye-Ying (Frontiers in Medicine, 2024)
Nocardia disease is an opportunistic infection, the occurrence is rare and mostly occurs in patients with immune deficiency. Even if the patient is immunocompetent, it can still be life-threatening. This case report describes a previously healthy 78-year-old male farmer with lung lesions discovered on a computerized tomography scan. Combined with the patient’s history of fever and the results of elevated laboratory markers associated with inflammation, the patient was diagnosed with a lung infection. After escalating empirical broad-spectrum antibiotics, antiviral and antifungal therapy, the patient continued to deteriorate to septic shock. In the meanwhile, the patient’s sputum was cultured repeatedly, and no obvious positive pathogenic bacteria were found. Considering the patient was elderly and that these lesions were solid with burr signs, as well as the progression after antimicrobial therapy cancer was considered in the differential diagnosis. Artificial intelligence (YITU, Hangzhou Yitu Medical Technology Limited Company) was also applied, and it also calculated that these lesions were cancerous. The patient received a puncture biopsy of the largest lung lesion. During the puncture pus was withdrawn from largest lung lesion. Culture and metagenome next-generation sequencing (mNGS) detection performed on pus indicated Nocardia otitidiscaviarum. The test report of the mNGS is also attached with a susceptibility report of commonly used clinical antibiotics to this Nocardia spp. Using this result, the patient’s disease was quickly controlled after selecting the targeted drug compound sulfamethoxazole and intravenous meropenem for treatment. In view of the high misdiagnosis rate and poor sensitivity of culture for Nocardia spp., this case emphasized mNGS playing a key role in the diagnosis and selection of effective antibiotics for the treatment of Nocardia spp. lung infections.